PERILAKU PETANI CABAI RAWIT TERHADAP RESIKO FLUKTUASI HARGA DI KECAMATAN GUMUKMAS KABUPATEN JEMBER - Aisyah Muluukhul Adriankurniawati; Imam Syafii; M Rondhi (University of Jember, 2017)
This study was aimed to determine the farmer’s behaviour in face of risk as result of pepper’s price fluctuation in Gumukmas District, Jember Regency. There are three criterias in farmer’s behaviour : risk lover, risk neutral, and risk averter. Thirty-nine farmers was selected by using simple random sampling. The utility function was employed to determine farmer’s behaviour. In this research, utility function with Bernoulli and Neuman -Morgerstern technique was used. This specification was modified with neutral probability (50:50). Estimation on this function was done by using uncertainty equivalent (CE) through quadratic estimation. The result showed that arround 33 farmers (84.62%) are risk neutral. The risk averter are 5 farmers (11.52%) and one farmer (2.56%) is risk lover. This result also showed that farmers with own land ownership status were more daring than farmers who own land tenure status, profit sharing, or farmers who have two land ownership status. Other results indicated that the farmers who pursued local pepperwere more daring than the farmers who pursued hybrid pepper or farmers who persuedlocal and hybrid at once.